2016
DOI: 10.1111/1755-5922.12189
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone Attenuates Doxorubicin‐induced Cardiotoxicity in Rats

Abstract: This study show that SP may have a protective effect on DOX-induced cardiotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…TUNEL) detecting DNA damage and fragmentation. Previously, many research groups examined the preventability of DNA damage in experimental DOX cardiomyopathy [7, 59, 63]. In accordance with their results, we successfully demonstrated that both the prophylactic and the conventionally scheduled therapy significantly reduce the degree of DNA fragmentation captured by TUNEL.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…TUNEL) detecting DNA damage and fragmentation. Previously, many research groups examined the preventability of DNA damage in experimental DOX cardiomyopathy [7, 59, 63]. In accordance with their results, we successfully demonstrated that both the prophylactic and the conventionally scheduled therapy significantly reduce the degree of DNA fragmentation captured by TUNEL.…”
Section: Discussionsupporting
confidence: 81%
“…Fibrosis represents another domain of DOX cardiomyopathy, which is also the subject of intensive preclinical research. Carvedilol [7], captopril [16], telmisartan [16] and spironolactone [63] have all been found to decrease DOX-induced myocardial fibrosis in small animals. Despite this, studies examining eplerenone gave either negative [12] or inconclusive results [13] when tested for the reversibility of DOX-induced interstitial fibrosis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been revealed that the expression of TGF-β1 was increased in the DOX-treated hearts [37]. Approaches that were used to reduce TGF-β1 also resulted in lower interstitial and perivascular fibrosis, along with less left ventricular dysfunction [38]. It has been revealed that mitochondrial reactive oxygen species-induced ERK1/2 activation was required for DOX-induced apoptosis and cardiotoxicity [39].…”
Section: Discussionmentioning
confidence: 99%
“…The exact molecular mechanisms underlying DOX-induced cardiotoxicity are complex and still not fully clarified. Studies have proposed that oxidative stress, inflammation, and apoptosis are the main players that control DOX pathogenesis 6. Excessive generation of free radicals during DOX metabolism augments oxidative stress, lipid peroxidation, membrane damage, and cardiomyocyte death 1.…”
Section: Introductionmentioning
confidence: 99%